2021
DOI: 10.3390/ijerph18115977
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Varicocele on Basic Semen Parameters, Sperm Nuclear DNA Dispersion and Oxidation-Reduction Potential in Semen

Abstract: Since varicocele is so common in infertile men, this study intends to analyse the relationships between varicocele and conventional semen characteristics, sperm nuclear DNA dispersion and oxidation-reduction potential (ORP) in semen. Varicocele-positive and varicocele-negative infertile men (study groups) showed significantly lower standard sperm parameters and higher sperm DNA fragmentation (SDF) and ORP in semen than healthy volunteers and subjects with proven fertility (control groups). A lower proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Not surprisingly, we observed chromatin/DNA damage in men exposed as well as not exposed to prolonged heat stress because DNA fragmentation in sperm cells can be induced by a variety of pathological and environmental factors [ 41 ]. In addition, it is known to be prevalent among men with poor semen quality [ 42 , 43 ]. However, to the best of our knowledge, this is the first study documenting an elevated sperm DNA fragmentation in the group of professional drivers, suggesting a potential link between heat stress and levels of ejaculated sperm DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, we observed chromatin/DNA damage in men exposed as well as not exposed to prolonged heat stress because DNA fragmentation in sperm cells can be induced by a variety of pathological and environmental factors [ 41 ]. In addition, it is known to be prevalent among men with poor semen quality [ 42 , 43 ]. However, to the best of our knowledge, this is the first study documenting an elevated sperm DNA fragmentation in the group of professional drivers, suggesting a potential link between heat stress and levels of ejaculated sperm DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 7 the major burst keywords in varicocele include diagnosis and treatment (e.g., evaluation colour Doppler flowmetry surgical technique artificial embolization); onset population (e.g., school child); male fertility impairment (e.g., complication sperm quality in vitro fertilisation [IVF] DNA fragmentation metabolism) which has similarity with the keyword clustering results derived from keyword (Figure 6). According to the above findings the main focus of current varicocele research is its surgical treatment method and effect on sperm quality with the correlation between varicocele and sperm DNA fragmentation being a current research hotspot that deserves the attention of relevant researchers (Gill et al, 2021). Varicocele can lead to decreased sperm quality and testosterone secretion through local tissue hypoxia elevated temperature and accumulation of metabolic waste which all lead to decreased fertility in men (Razi et al, 2021)…”
Section: Resultsmentioning
confidence: 99%
“…Varicocele (VC) is a common disease in male infertility in which the internal spermatic vein malformation is twisted, dilated, and elongated 1 . The prevalence of VC in the general population is approximately 15%, and in infertile males, it is approximately 35% 2,3 . VC is a common aetiology of male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of VC in the general population is approximately 15%, and in infertile males, it is approximately 35%. 2,3 VC is a common aetiology of male infertility. Studies have shown that VC plays a role in decreased testicular function, leading to spermatogenic dysfunction and diminished testosterone levels.…”
Section: Introductionmentioning
confidence: 99%